Silk fibroin/methacrylated gelatine/hydroxyapatite biomimetic nanofibrous membranes for guided bone regeneration - Li, Bo; Chen, Ying; He, Jisu; Shu, Yue; Yang, Haocheng; Liu, Junhong; Zhang, Chi; Xiao, Wenqian; Liu, Zhongning; Liao, Xiaoling (International journal of biological macromolecules, 2024)
By mimicking in vivo bionic microenvironment and promoting osteogenic differentiation, the hybrid organic-inorganic nanofibrous membranes provide promising potential for guided bone regeneration (GBR) in the treatment of clinical bone defects. To develop a degradable and osteogenic membrane for GBR by combining the natural biomacromolecule silk fibroin (SF) and gelatine with the bioactive nano hydroxyapatite (nHA), the anhydride-modified gelatine-nano hydroxyapatite (GelMA-nHA) composites were synthesized in situ and introduced into silk fibroin to prepare nanofibrous membranes with different ratios using electrospinning and photocrosslinking. The nanofibrous membranes, particularly those with a mass ratio of 7:2:1, were found to exhibit satisfactory elongation at break up to 110 %, maintain the nanofibrous structure for up to 28 days, and rapidly form bone-like apatite within 3 days, thus offering advantages when it comes to guided bone regeneration. In vitro cell results showed that the SF/GelMA/nHA membranes had excellent biocompatibility and enhanced osteogenic differentiation of hBMSCs. In vivo studies revealed that the hybrid composite membranes can improve bone regeneration of critical-sized calvarial defects in rat model. Therefore, the novel hybrid nanofibrous membrane is proposed to be a alternative candidate for creating a bionic microenvironment that promotes bone regeneration, indicating their potential application to bone injury treatment. •SF and GelMA nanofibrous -membranes containing nHA were prepared by electrospinning and photocrosslinking.•This novel nanofibrous membrane has -satisfactory mechanical strength and degradation rate.•This novel biomimetic SF/GelMA/nHA membrane provides a promising strategy to enhance bone regeneration.